PERANCANGAN OUTERWEAR UNTUK PRIA SEBAGAI PENUNJANG KEGIATAN TOURING SEJARAH BANDUNG - Septiarashinta, Septiarashinta; Bastaman, Bastaman (Serat Rupa: Journal of Design, 2022)
Bandung known has many historic relics. It made public high interest in historical tourism and the beginning of many historical communities in Bandung with visiting historical sites as main activities, one of which is the Aleut Community. Aleut pioneered a program called Ngaleut, visit the historical sites on a walk and has been adapted by other historical communities. Then, Aleut came with a similiar activity, which called Momotoran, visiting historical sites using motorbike touring method with the aim of exploring historical sites further. The high demand of historical tourism makes the concept of Momotoran potential to be adapted by other communities such as Ngaleut, so there is an opportunity to create products for these activities, outerwears in the form of jackets and vest. Made by fulfill the needs of Momotoran activities, from the functional aspect to protect the body, the structural aspect by using simple cutting, and the decorative aspect due to the need to embed an identitiy as a historical community like the community in general. This study uses qualitative methods with data collected from literature studies, interviews, and observations through social media. This research is also exploring elements on the “Monumen Perjuangan Rakyat Jawa Barat” to be used as decorative element that are applied through the polyflex printing technique. This research is expected to be a reference for outerwear designs for historic touring or similiar activities.